Synthesis and spectroscopic characterization of a fluorescent phenanthrene-rhodamine dyad for ratiometric measurements of acid pH values. (21st June 2021) - Srivastava, Priyanka; Fürstenwerth, Paul Christian; Witte, Jan Felix; Resch-Genger, Ute
Abstract : Ratiometric pH sensing by multichannel emission response utilizing excimer/monomer emissions of phenanthrene and rhodamine emission at single excitation wavelength. Abstract : We present the rational design, synthesis and spectroscopic characterization of a novel dual excitation, three color emitting, pH-responsive fluorescent probe consisting of two phenanthrene and one rhodamine B units linked by click chemistry. The rhodamine moiety, excitable at λ Ex = 315 nm and at λ Ex = 560 nm in its ring-opened form, provides the pH-responsive fluorophore, while the pH-insensitive phenanthrene, excited at λ Ex = 315 nm, serves as inert internal reference, The presence of two phenanthrene moieties enables a blue monomer and a blueish green excimer emission at 351 nm and 500 nm, respectively. Opening of the rhodamine B spirolactam ring at an acidic pH below 5.0 (p K a = 2.59 ± 0.04) switches on its emission at 580 nm. Simultaneously, the phenanthrene excimer emission decreases caused by a change in orientation of the phenanthrene units, while the monomer emission is barely affected. This sensor design enables ratiometric measurements in the low acidic pH range utilizing the intensity ratios of the rhodamine B and phenanthrene excimer emission at 580 nm and 500 nm. Alternatively, also the intensity ratios of the rhodamine B and the phenanthrene monomer emission could be exploited or the sum of the phenanthrene monomer and excimer fluorescence. To the best of our knowledge, this is the first report of ratiometric sensing utilizing such a versatile type of tricolor emissive dyad probe bearing phenanthrene moieties and showing phenanthrene monomer and excimer emission.